Rendering International Human Rights Law Fit for Purpose on Climate Change. (8th January 2023) - Venn, Alice
Abstract: The present article addresses the unique legal and operational challenges encountered in the adoption of a human rights-based approach to climate change under international law. It examines the suitability for purpose of the international human rights regime and outlines the key steps to be taken in the requisite advancement of recourse to justice in climate matters. Five central challenges are addressed, namely, of the exclusivity of climate law and international human rights law, the operational barriers within the UN human rights system, specific legal challenges facing the UN Treaty Body mechanisms, the causation challenges associated with attributing responsibility for climate harm to states and, finally, the extraterritorial application of international human rights law. These challenges represent some of the most significant hurdles emerging through the literature and practice, which need to be overcome to enable international human rights law to better provide recourse to justice to climate-vulnerable states, groups and individuals.